2021
DOI: 10.1038/s41598-021-87191-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain electrical traits of logical validity

Abstract: Neuroscience has studied deductive reasoning over the last 20 years under the assumption that deductive inferences are not only de jure but also de facto distinct from other forms of inference. The objective of this research is to verify if logically valid deductions leave any cerebral electrical trait that is distinct from the trait left by non-valid deductions. 23 subjects with an average age of 20.35 years were registered with MEG and placed into a two conditions paradigm (100 trials for each condition) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Visual inferences in both experimental conditions are processed fundamentally in the left hemisphere, as some other cerebral studies on deduction have shown (J. Prado, 2018;Reverberi et al, 2012;Salto et al, 2021). In this study, there is no electrical evidence of deductive core areas in the valid condition, but beta-2 oscillations coincide with opercular and triangular activity described by deductive meta-studies (Li Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Visual inferences in both experimental conditions are processed fundamentally in the left hemisphere, as some other cerebral studies on deduction have shown (J. Prado, 2018;Reverberi et al, 2012;Salto et al, 2021). In this study, there is no electrical evidence of deductive core areas in the valid condition, but beta-2 oscillations coincide with opercular and triangular activity described by deductive meta-studies (Li Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Signi cantly, left frontal and parietal regions do not show statistically signi cant differences between the two conditions (See Figure S4 in Supplementary Material). Previous studies have associated increased beta-2 activity and connectivity with logically valid inferences (Salto et al, 2021) also in opercular and triangular areas. There are no differences in theta band activity between conditions, suggesting their similar visuo-semantical processing.…”
Section: Discussionmentioning
confidence: 92%
“…Beta oscillations accompanying positive (negation free) logical operators (conjunction, disjunction, material conditional) have been reported in the literature in semantical [ 84 ] and visuo-semantical contexts (Álvarez-Merino, 2019). Two other experiments with the same SET paradigm applied in MEG studies on amplitude [ 83 ] and connectivity (to appear) found similar beta-2 activations at the early stages of the deductive inferential process. The second time region of differences in beta-2 (see Figs.…”
Section: Discussionmentioning
confidence: 74%
“…The spatial limitations of EEG measures notwithstanding, there are important facts about the spatial distribution of beta-2 in the left central and left temporal regions since its presence throws some light on the cortical relationships between language and valid deductive inference. Visual inferences in both experimental conditions are processed fundamentally in the left hemisphere, as some other cerebral studies on deduction have shown [ 24 , 33 , 83 ]. In this study, there is no electrical evidence of deductive core areas in the valid condition, but beta-2 oscillations coincide with opercular and triangular activity described by deductive meta-studies [ 19 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation